Isolation and Evaluation of Antifungal Activity of Sand Sea Cucumber Symbiont Bacteria (Holothuria scabra) from Wakatobi National Park against Malassezia furfur - Yanti, Nur Arfa (LenteraBio : Berkala Ilmiah Biologi, 2024)
Malassezia furfur is a fungus that causes tinea versicolor which requires antifungal compounds for treatment. Antifungal compounds can be obtained from bacteria that are in symbiosis with marine organisms. One candidate for bacteria producing antifungal compounds is the sand sea cucumber symbiont bacteria (Holothuria scabra). This research aims to obtain bacterial isolates that are able to inhibit the growth of the Malassezia furfur fungus that causes tinea versicolor (Pityriasis versicolor). Isolation of sea cucumber symbiont bacteria was carried out using the pour plate method. The antifungal activity of symbiont bacteria was carried out using the well diffusion method. The results of the research obtained 5 isolates of the sand sea cucumber symbiont bacteria which had M. furfur antifungal activity. Three bacterial isolates, namely isolates DT1, DT4 and isolate DT5, produced antifungal compounds which were able to inhibit the growth of M. furfur with an inhibition zone ranging from 8.60 mm-11.30 mm within 24 hours. Based on the identification results using the profile matching method, it is known that the bacterial isolates DT1 and DT5 belong to the genus Pseudomonas, while the bacterial isolate DT4 belongs to the genus Bacillus. Therefore, the three isolates of sand sea cucumber symbiont bacteria can be developed and applied to produce medicinal ingredients for tinea versicolor skin disease.